ANALISIS KOMUNIKASI PERSUASIF SEBAGAI UPAYA MEMENANGKAN HATI PEMILIH PADA PILBUP KABUPATEN SOLOK (ANALISIS ISI PADA AKUN TIKTOK @JONFPANDU) - Arianto, Arianto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The development of digitalization technology or the 4.0 era has changed the landscape of political campaigns in Indonesia, one of which is the use of social media (TikTok) as the main means of building an image, increasing trust and efforts to win the hearts of voters in the 2024-2029 regent elections in Solok Regency. The purpose of this study is to analyze persuasive communication techniques and analyze persuasive messages in influencing voter perceptions and preferences. This study uses a qualitative approach with a content analysis method. The results of the study obtained the dominant persuasive communication techniques used by Jon Pandu in his political campaign in Solok Regency in building credibility, trust, and public support in influencing voters' hearts are integration techniques and reward techniques, these techniques are influenced by Jon Pandu's communication which emphasizes that he is part of the Solok Regency community to build his hometown better and provide a positive impact on those who choose him, so that these techniques can build a sense of trust, closeness, and solidarity. Jon Pandu's persuasive messages are strategically designed to form a positive image, build emotional closeness, and arouse the participation of the people of Solok Regency through an inclusive approach, with local nuances, and connected to national political power, so that it becomes the key to influencing voter perceptions and preferences ahead of the Pilkada.Keywords: Persuasive Communication, Persuasive Techniques, Political Communication, New Media